(1)

(1)   

x+y =9

x=y+ 3

(2)   

r= 2q

4q+r = 12

(3)   

m+n= 0

m= 5n−30

(4)   

x+ 2y= 0

x= 2y−4

(5)   

−4x+y =−6

y = 2x

(6)   

−4p+q=−6

(2)

(1)  

x+ 2y = 8

7x10y =40

(2)  

13x−9y= 106

10x+ 3y= 22

(3)   

3s+ 2t = 12

2s+t = 8

(4)   

7a+ 5b=55

5a+b=29

(5)   

a+ 2b= 0

5a+b=27

(6)   

(3)

(1)   

p+q = 5

2p+ 3q = 14

(2)   

−3a+ 4b=−26

a+ 6b=28

(3)   

6a+ 2b=8

5a−21b= 84

(4)   

−3m−5n= 15

−2m−14n= 74

(5)   

−10m+ 2n= 34

−7m+ 9n= 39

(6)   

7x3y= 11

(4)

(1)   

x+y =9

x=y+ 3

(2)   

r= 2q

4q+r = 12

(3)   

m+n= 0

m= 5n−30

(4)   

x+ 2y= 0

x= 2y−4

(5)   

−4x+y =−6

y = 2x

(6)   

−4p+q=−6

(5)

(1)   

x+ 2y = 8

7x10y =40

(2)   

13x−9y= 106

10x+ 3y= 22

(3)   

3s+ 2t = 12

2s+t = 8

(4)   

7a+ 5b=55

5a+b=29

(5)   

a+ 2b= 0

5a+b=27

(6)   

−a+b= 6 3a+ 2b=3

(6)

(1)  

p+q = 5

2p+ 3q = 14

(2)  

−3a+ 4b=−26

a+ 6b=28

(3)   

6a+ 2b=8

5a−21b= 84

(4)   

−3m−5n= 15

−2m−14n= 74

(5)   

−10m+ 2n= 34

−7m+ 9n= 39

(6)   

7x3y= 11

−5x+ 4y=−6

Updating...

Updating...